Muscari pamiryigidii (Asparagaceae, Scilloideae), a new species from northwestern Anatolia - Eker İsmai̇l (Phytotaxa, 2019)
A new species from Turkey, Muscari pamiryigidii Eker sp. nov. (Asparagaceae), is described and illustrated here. Diagnostic characters, description, original photographs, detailed illustration, geographical distribution, conservation assessment, observations, and taxonomic comments on the new species are presented. The new species is compared to the closely related species M. armeniacum, M. aucheri and M. bourgaei.